PEMANFATAAN KAWASAN HUTAN NEGARA OLEH MASYARAKAT ADAT DI DESA MATOTONAN KECAMATAN SIBERUT SELATAN KABUPATEN KEPULAUAN MENTAWAI - Juni Arman; Afrizal Afrizal; Asrinaldi Asrinaldi (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2018)
This research is motivated by the use of state forest areas in the buffer zone of Siberut National Park by the Matotonan Indigenous People. In fact, the Mentawai Islands Regency consists of 82% of the state forest area and only 18% of the Other Use Areas are space for the community, placing the country in a dominant regulation on the use of forests in Mentawai. But until 2016, 79% of the forest area on Siberut Island was controlled and utilized by indigenous peoples. The Matotonan indigenous people utilize state forest areas more dominantly as spiritual needs rather than as economic needs. With the belief that indigenous peoples are experts in preserving forests, the government provides space for indigenous peoples to utilize state forest areas with the issuance of regional regulations on the recognition and protection of Uma as a customary law community unit. Thus, when the state views forest use in accordance with its interests and objectives, the government responds positively to the use of state forest areas by indigenous peoples.